2013
DOI: 10.4038/sljid.v3i1.4717
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study to determine antimicrobial activity of selected Ayurvedic preparations against bacteria and fungi causing superficial skin infections

Abstract: The increasing antimicrobial resistance exhibited by microorganisms causing superficial skin infections has led to extensive research on the therapeutic potential of Ayurvedic preparations. Medicinal plants contain many types of naturally occurring and side effectsfree anti microbial compounds that can be effectively used against microbial infections. We tested the antimicrobial activity of twenty-eight Ayurvedic preparations used to treat superficial infections in a local Ayurvedic healthcare institution. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The release profile of SEC-LDH shows a high initial drug release rate in the first 3 h and then reaches an almost constant level over a longer period, which confirms the slow and sustained release of the drug. Such a release profile is characteristic of a diffusion-controlled release process [ 20 ].
Fig.
…”
Section: Characterization Of Selectively Encapsulated Curcuminoids (Smentioning
confidence: 99%
“…The release profile of SEC-LDH shows a high initial drug release rate in the first 3 h and then reaches an almost constant level over a longer period, which confirms the slow and sustained release of the drug. Such a release profile is characteristic of a diffusion-controlled release process [ 20 ].
Fig.
…”
Section: Characterization Of Selectively Encapsulated Curcuminoids (Smentioning
confidence: 99%
“…Its antimicrobial activity against C. albicans and dermatophytes have been reported using the agar well diffusion assay. 18 In this in-vitro study Triphala was found to show activity against C. albicans, C. tropicalis, C. parapsilosis, S. aureus, MRSA, S. epidermidis, and P. aeruginosa planktonic cells. Antibiofilm activity of Triphala has been reported which suggests its usefulness as a general antiseptic with low side effects.…”
Section: Discussionmentioning
confidence: 86%
“…It is reported to have anti-inflammatory, antioxidant, and antimicrobial activity against a wide spectrum of microorganisms including bacteria, yeasts and dermatophytes. 18,19,11 The active phytochemicals contributing to antimicrobial activity are tannic acid, chebulic acid, and flavonoids. Its antimicrobial activity against C. albicans and dermatophytes have been reported using the agar well diffusion assay.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Studies on medicinal plants used in ayurvedic or traditional treatment have demonstrated their potential as antimicrobials. [ 2 ] Phytochemicals obtained from medicinal plants have been used widely in the development of novel therapeutic agents including antimicrobial agents. The antimicrobial activity of several medicinal herbs used in traditional and ayurvedic medicine in Sri Lanka have been reported.…”
Section: Introductionmentioning
confidence: 99%